Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan Perusahaan PT Angkasa Pura II Ketika Pandemi COVID-19 Periode 2019-2022 - Bachtiar, Muhammat Feril Yusuf; Andityo Pujo Laksana (Jurnal Manajemen Dirgantara, 2024)
This research aims to describe the condition of memories at the PT Angkasa Pura II company based on four ratio analyses in the 2019–2022 period. The objects used in this thesis are financial reports in the form of financial position reports, profit and loss reports, and cash flow reports for PT Angkasa Pura II for the 2019–2022 period. The data analysis method used is ratio analysis, which consists of liquidity analysis, solvency analysis, activity analysis, and profitability analysis, which is then determined by the level of financial performance by referring to the decision of the Minister of State-Owned Enterprises of 2002, Number KEP-100/MBU/2002. The results of the research show that the financial condition of PT Angkasa Pura II from 2019 to 2022 is experiencing an unfavorable condition in terms of the four ratios. By obtaining the BBB category with the unhealthy predicate in 2019 and the B category with the unhealthy predicate from 2020 to 2022.